Photodegradation of methylene blue in aqueous media using titanium dioxide-based heterogeneous photocatalysis under natural light. - Bernido, Julidyn Puragan (2015.)
This study developed two heterogeneous TiO2-based phtocatalysts: pure TiO2 and Fe-doped TiO2 (Fe-TiO2). heterogeneous catalysts were prepared by coating TiO2 and Fe-TiO2 powder on glass beads. The photocatalytic activity of both heterogeneous photocatalysts were studied by photodegredation of mythelene blue in aqueous solution under two pH conditions ( 6 and 9) and two ionic concentration conditions (0 and 38 ppt)., The Fe-TiO2 powder contained minimal amount (2.245 percent) of Fe as expected. However, surface functionality and ultraviolet-visible (UV-Vis) profile of both TiO2 and Fe-TiO2 powder were very similar indicating that doping did not alter these properties. Between the two heterogeneous catalysts prepared, the amount of Fe-TiO2 catalyst coated on glass beads was lower compared to pure TiO2. The removal of mythelene blue was significantly affected by ionic concentration which removal is higher at lower ionic concentration (0ppt). Although it appeared that the removal of mythelene blue was higher at pH 9, statistical analyses revealed that the effect was not significant. In addition, the removal of mythelene blue by the two catalysts were significantly different. Heterogeneous photocatalyst based on pure TiO2 showed higher removal of methylene blue in all pH and ionic concentration. Moreover, no interactive effects between variables were observed. Lastly, the blank showed no significant difference on the removal of mythelene blue with the heterogeneous photocatalysts which suggest that degradation by direct photolysis from sunlight could be the reason for this result.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Photodegradation